Reconhecendo a geometria espacial: uma proposta de ensino a partir de atividades contextualizadas - Moraes, Lucas Garcia de (2019)
The inspiration for this work comes from the observation in the difficulties of the majority of the students of the CEEJA in finding the literal sense of the study of the spatial geometry. In order to contribute to the development of the necessary skills to better understand the geometric concepts, we restructure a workshop a workshop related to the theme, giving it a new focus and searching through it, analyze the development of the participating students with the intent to respond the following question: do the practical activities bring significant results in the Youth and Adult Education of the CEEJA? All the elaboration of this work was carried out in agreement with the PCN, the resolution SE 75/2018 that regulates on the organization of the EJA courses, in the State Centers of Education of Youths and Adults, besides the internal rules of the CEEJA - Votorantim, place where all this happened. We carried out a survey on the profile of the students enrolled, as well as an analysis of the work already done in the place. The research on the profile of the students was carried out during the year of 208 in the act of enrollment of each one of them and the group that integrated the workshop was formed by students who registered by their own will, all the way when we arrived at the mark of 32 enrolled, we closed the inscriptions so that a very large group did not form, since this could hinder our analysis. The data collection was according to the devolution of the requested tasks to the students and we ended up making a comparison with the final results obtained by these students with the results of another group of students who did not participate in the workshop.